Essays on trade restrictiveness and quality upgrading - Niu, Zhaohui (2016)
In recent decades, through several rounds of trade negotiations, tariff rates have been substantially reduced. As a result, non-tariff measures (NTMs) have become increasingly important, as policy-makers jostle to find alternatives to the tariff reduction. This thesis aims to examine the effect of NTMs on international trade and to explore how import competition measured by overall protection (i.e. tariff and AVEs of NTMs) affects product quality upgrading. The thesis consists of three empirical studies to examine these issues. The first study analyze the evolution of the incidence and intensity of NTMs. Building on Kee, Nicita and Olarreaga (2009), we estimate the ad valorem equivalents (AVEs) of NTMs for 53 countries at product level for multiple years over the period 1997 to 2012. This study extends Kee et al. (2009) by adding a time dimension and applying the NTM from a newly available database. The study suggests that the incidence and the protection level of NTMs were both increasing during this period; hence, NTMs have become the major source of trade protection. By adding tariff to the AVEs of NTMs as the overall protection, this study also analyzes the evolution of overall protection. The results show that the overall protection level, for most countries and products, has not decreased as tariff has. This means the overall protection has stayed constant or been increasing, and in turn suggesting the expected trade liberalization from the trade negotiations in recent decades has been partly nullified. The second study investigates whether governments are applying NTMs to substitute for tariff, building on the theoretical model in Essaji (2010) and the empirical framework in Kee and Neagu (2011) and Ronen (2014). With the estimated AVEs of NTMs for every three years during the period of 1997 to 2012, the second study explores the relationship between tariffs and NTMs in both levels and changes. The study finds a generally substitutable relationship between tariffs and NTMs, both statically and dynamically, and the results are robust to various robustness checks. The third study investigates the non-monotonic relationship between import competition and quality upgrading, as an extension of Amiti and Khandelwal (2013). With import competition measured by overall protection instead of tariff rate, as in Amiti and Khandelwal, this study questions whether tariff is an adequate measure for import competition in light of recent tariff reduction and the substitution uncovered between tariff and NTMs. In their study, Amiti and Khandelwal find that after import competition increases, firms close to the world technology frontier would innovate more while firms distant from the technology frontier are less likely to innovate. However, in our analysis, the two effects are insignificant when import competition is measured by overall protection, and the results remain so even after various robustness checks. Hence, tariff is found to be an inadequate measure for import competition.